The Spring Festival Is Associated With Increased Mortality Risk in China: A Study Based on 285 Chinese Locations - He, Guanhao; Cai, Min; Meng, Ruilin; Hu, Jianxiong; Peng, Ke; Hou, Zhulin; Zhou, Chunliang; Xu, Xiaojun; Xiao, Yize; Yu, Min; Huang, Biao; Lin, Lifeng; et al. (Frontiers in Medicine, 2022)
Background: The Spring Festival is the most important traditional festival in China. This study aimed to estimate the mortality risk attributable to the Spring Festival. Methods: Daily meteorological, air pollution and mortality data were collected in 285 locations in China from 2013 to 2017. The Spring Festival was divided into three periods: pre-Spring Festival (16 days before Lunar New Year’s Eve), mid-Spring Festival (16 days from Lunar New Year’s Eve to Lantern Festival), and post-Spring Festival (16 days after Lantern Festival). Mortality risk attributed to the Spring Festival in each location was first evaluated using a distributed lag non-linear model, and then they are pooled using a meta-analysis model. Results: We observed a dip/rise mortality pattern during the Spring Festival. Pre-Spring Festival was significantly associated with decreased mortality risk (ER: -1.58%, 95%CI: -3.09%--0.05%), and mid-Spring Festival was unrelated to mortality risk, while post-Spring Festival was significantly associated with increased mortality risk (ER: 3.63%, 95%CI: 2.15%-5.12%). Overall, the 48-day Spring Festival period was associated with a 2.11% (95%CI: 0.91-3.33%) increased mortality. We also found that the elderly aged over 64 years old, females, people with CVD and people living in urban area were more vulnerable to the Spring Festival. Conclusion: Our study found that the Spring Festival significantly increased mortality risk in China. The findings suggest that it is necessary to develop clinical and public health policy to alleviate the mortality burden associated with the Spring Festival.